2016
DOI: 10.1016/j.juro.2015.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Genomic Classifier for Predicting Post-Prostatectomy Recurrence in a Community Based Health Care Setting

Abstract: Decipher improves our ability to predict clinical recurrence in prostate cancer and adds precision to conventional pathological prognostic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Expression profiling, specimen selection, RNA extraction and microarray hybridization were done in a Clinical Laboratory Improvement Amendments (CLIA)-certified laboratory facility (GenomeDx Biosciences, San Diego, CA, USA) as previously described (14). Briefly, total RNA was extracted and purified using the RNeasy FFPE kit (Qiagen, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Expression profiling, specimen selection, RNA extraction and microarray hybridization were done in a Clinical Laboratory Improvement Amendments (CLIA)-certified laboratory facility (GenomeDx Biosciences, San Diego, CA, USA) as previously described (14). Briefly, total RNA was extracted and purified using the RNeasy FFPE kit (Qiagen, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have externally validated this biomarker signature to predict clinical recurrence in a community setting,[24] metastatic progression,[22, 25-27] and PCSM after radical prostatectomy. [28, 29] These validation studies have shown good discriminatory ability of the test with the AUC ranging between 0.75 and 0.82.…”
Section: Currently Available Testsmentioning
confidence: 99%
“…Almost all studies compared the discriminatory ability of the GC score to clinical prognostic models such as the Cancer of the Prostate Risk Assessment postsurgical (CAPRA-S),[14] Stephenson nomogram,[15] and Eggener risk model[16] demonstrating improved prognostic discrimination when combined. [24-26, 28, 29]…”
Section: Currently Available Testsmentioning
confidence: 99%
“…This test has subsequently been validated in several additional cohorts [38,39,40 & 43]. The score is continuous but cut points of less than 0.45, 0.45-0.6, and more than 0.6 have been designated as defining a low-, intermediate-, and high-risk group, respectively.…”
Section: Genomic Classifiermentioning
confidence: 99%